Urogynecology service at a district general hospital in the United Kingdom - Changing needs or a better understanding? - Farah Wali Lone; Ainharan Raveendran (Wolters Kluwer Medknow Publications, 2019)
Context: The urogynecological problems in women increase with age. The National Health Services (NHS) is experiencing an increase in the demand for and costs of health and social care for women in midlife. It is a relatively new subspecialty which requires a holistic approach to a patient symptoms and expert skills to overcome demands from aging female population and fulfilling patient expectations. Aims: The aim of the study was to analyze the referral pattern in relation to urogynecological symptoms referred to district general hospital in the United Kingdom and in turn to understand the gravity of the situation for improving the care of these women. Subjects and Methods: This was a retrospective study of case notes of women attending the gynecological outpatient clinic led by an urogynecology subspecialist at district general hospital in the United Kingdom having attended the clinic with symptoms suggestive of pelvic floor dysfunction. Results: We identified 777 women who attended the clinic with symptoms of pelvic floor dysfunction. The most frequently stated reason for referral was pelvic organ prolapse, followed by primary urinary incontinence. Majority of the patients (44%) had prolapse at diagnosis and 26% of the patients had multiple symptoms related to pelvic floor dysfunction after a urogynecologist's consultation, 5% of the patients had combined symptoms diagnosed at urogynaecology clinic. Majority of the referrals were from the general practitioners (43%). Conclusions: The study revealed that health practitioner referring the women needs better understanding of the urogynecological symptoms and with a better understanding and a thorough symptom treatment can be initiated for various symptoms at the same time. This allows patients' multiple symptoms improvement, avoids repeat referrals from primary care, avoids repeat visits to the clinics, avoids repeat interventions, and improves patients' satisfaction and therefore saves NHS resources.